"Shock Packs": Audience Responses to Health Canada's Graphic-Image Health-Warning Labels on Tobacco Product Packaging - de, Laat Sonya (My University, 2003)
Canada, the first country to implement graphic-image health-warning labels on tobacco-product packaging, has been hailed as a world leader in tobacco-reduction strategies. Health Canada's intention with the warning labels is to encourage smokers to reduce the amount of tobacco they use or altogether quit smoking, and to prevent non-smokers from starting to smoke. Using semiotics, a multi-sited ethnographic approach and media ethnography, I analysed the responses of members of the target audience to look at how their interpretations of the labels affect their everyday lives. I found that all the smokers I interviewed have been feeling stigmatised as a result of this warning label campaign and the anti-smoking environment in which they reside. Established smokers and those long-time smokers who have recently quit smoking feel this stigma to a much higher degree than do younger people who have smoked for less than a decade. Looking at the "preferred readings" of the labels in conjunction with the context in which individuals interpret and internalise the meaning they derive from the intended messages, I found that some older individuals have been able to reduce, downplay, or contest the stigma by relocating themselves into locales and identities where they can be accepted as smokers. Younger smokers have been able to apply the "preferred reading" of a few labels to the entire campaign, thus dismissing the warnings entirely and avoiding the full weight of the stigma. I conclude with a discussion of the ways Health Canada can look towards tobacco company marketing practices and the efforts of other health promoters to produce tobacco-reduction strategies, including labelling campaigns, that do not generate feelings of fear, guilt and stigmatisation in smokers, but instead offer positive encouragement and alternatives to tobacco-use.
Keywords: Anthropology; Anthropology